Fitase em dietas para frangos de corte - Broch, Jomara (2019)
The aim of this study was to evaluate the effects of phytases in broiler’s diets. In the first experiment, five treatments were distributed in a completely randomized design, with eight replications. The treatments consisted of a positive control diet (PC), a negative control diet (NC); and the NC diet + 0, 1000, 2000 or 3000 FYT kg-1 phytase. From 1 to 21 days of age, weight gain (WG), feed intake (FI) and feed conversion ratio (FCR) raised due to the increasing levels of phytase (P<0.05), and from 1 to 42 days the best results for WG, FI and FCR were obtained using 2051, 1992 and 2101 FTY kg-1, respectively. At 42 days of age, the highest Seedor Index (SI) and dry matter (DM) values were obtained with 1553 and 1765 FTY kg-1, respectively. At 21 days of age, blood calcium (Ca) content decreased with increasing phytase. Blood phosphorus (P) exhibited quadratic behavior, with the maximum recorded at 1680 FYT kg-1 phytase. Tibia Ca raised due to the increasing phytase at 21 days of age (P<0.05). The apparent ileal digestibility coefficients of dry matter, mineral matter, crude protein and crude energy showed quadratic responses, with the highest coefficients obtained for the inclusion of 1164, 1592, 1085 and 1342 FYT kg-1 phytase, respectively. A high dose of 2973 FYT kg-1 had the best WG from 1 to 21 days of age. From 22 to 42 days, 2051 FYT kg-1 and 2101 FYT kg-1 showed the best WG and FCR, respectively. The second and third experiments were divided into two phases (1-21 and 22-42 d). Fifteen treatments were distributed in a 3x5 factorial arrangement, with high (HP), medium (MP) and low (LP) phytate and PC, NC (reduction of 0.15% of Ca and P) and NC diet plus 0, 500, 1000 or 1500 FTU kg-1 of phytase. From 1 to 21 days of age, FI peaked with supplementation of 1051 FTU kg-1 phytase to the LP diets. BA of broilers receiving LP showed a maximum response at 1101 FTU kg-1. Ca blood had a linear behavior for broilers fed with HP and quadratic for those into LP treatments. Blood P showed quadratic responses for broilers fed HP, MP and LP diets. Ca tibia content of broilers receiving LP diets had a linear response, increasing phytase levels increased Ca content (P<0.05). In general, bone P of birds fed with diets containing HP was higher than those into LP or MP diets (P<0.05). Phytase supplementation improves the performance and bones of birds. The use of 1101 FTU kg-1 is advised for better bone characteristics in LP diet. At 42 broilers WG, BS and DM were lower compared to the PC, by Dunnett’s Test. Serum Ca and P of birds of HP group receiving the NC and NC + 500 FTU kg-1 had a higher concentration (P<0.05) than LP. Bone P of birds fed with diets containing LP had a quadratic behavior (P<0.05) and the levels that provided the maximum response were 470 FTU kg-1. Phytase supplementation had a positive response in diets with reduced Ca and P. Phytase improves broilers performance based on regression analysis, with 952 FTU kg1 without having a negative impact on the other parameters evaluated.